The Early Detection and Stimulation of Growth and Development in Toddlers in Sidorahayu Wagir Village, Malang Regency - Ernawati, Naya; Solikhah, Fitriana Kurniasari (Tarqabin Nusantara Group, 2024)
Early age, especially the first 1000 days of life, is an important time for brain development, which includes physical, language, cognitive and socio-emotional development. Screening is just a routine procedure in daily child growth and development checks, which can provide clues if there is something that needs attention. The aim of this service is to detect early growth and development disorders in toddlers and provide education to cadres and parents about the importance of regularly checking their children's growth and development and the importance of providing stimulation. The target of this activity is cadres and parents of toddlers who have toddlers aged 3-60 months. The method used in the activity is the KPSP child growth and development detection instrument and to increase parents' knowledge about growth and development, it is carried out through counseling, question and answer discussions and demonstrations on how to stimulate children's growth and development. The results of early detection of growth assessment using the WHO curve showed that 27 children (90%) were of normal stature and normal nutrition and 3 children (10%) were malnourished. For examining children's development using the KPSP instrument, the results were 25 children (83%), with appropriate development. and 5 children (17%) with questionable development. Providing education related to growth and development and stimulation for toddlers is important for cadres and parents in an effort to optimize the growth and development of toddlers to welcome the golden generation.